P82 What is the role of chest computed tomography in children with parapneumonic effusion?. (16th November 2010) - Parmar, A; Peek, G; Firmin, R; Pandya, H; Gaillard, E
Abstract : Introduction: The incidence of parapneumonic effusion in children has been rising in the UK since the mid 1990s (1). There is anecdotal evidence that the number of complicated cases with more severe illness may be increasing. This is frequently due to severe underlying, often necrotic pneumonia, caused by unusual organisms (2), pulmonary abscesses or bronchopleural fistulas. Chest ultrasound does not reliably identify these processes and CT scanning is the investigation of choice. However, there has been little research in the use of chest CT in children with parapneumonic effusion and its use remains controversial. Aims: To evaluate the usefulness of chest CT in children with parapneumonic effusion. Methods: We retrospectively reviewed the medical notes and imaging of all children admitted between January 2004 and December 2009 with a diagnosis of parapneumonic effusion to the University Hospitals of Leicester NHS Trust. Results: A total of 183 children were identified. Of this number, 51 children underwent CT scanning. The main indications for chest CT were as follows: slow/no response to IV antibiotic treatment (25%), failed attempt at chest drainage without urokinase (24%) and acute critical clinical deterioration (16%). Other indications included failure of chest drainage with urokinase, failure of surgical intervention or investigation for other pathology. A range of pathological findings were identified with CT. 38% of the CT scans identified collapse consolidation. Other pathology was also identified that was not apparent on ultrasound scan. 4% identified pulmonary abscess, 4% identified areas of lung necrosis, 4% identified broncho-pleural fistula and 6% identified cavitating pneumonias. Conclusion: (1) A chest CT is useful in children with a complicated parapneumonic effusion to detect lung pathology not readily detected with chest ultrasound. (2) A small number of children have a pulmonary abscess complicating the parapneumonic effusion. (3) Further research is needed to establish the role and timing of chest CT scanning in children with infective pleural disease.